Social Justice Advocacy Training: An Innovative Certificate Program for Counselor Education - Katherine A Feather; Tiffany M. Bordonada; Kimberly A Nelson; Kathy M Evans Ph.D (Teaching and Supervision in Counseling, 2019)
The authors outline an innovative certificate program that promotes the Multicultural and Social Justice Counseling Competencies (MSJCC; Ratts, Singh, Massar-McMillan, Butler, & McCullough, 2015) and how counselor education programs can commit to a social justice approach. In addition, the authors provide a detailed summary of the certificate program that requires counselors-in-training to move beyond a multicultural understanding of diverse cultural worldviews so that they commit to becoming social change agents and take action on issues of equality and justice. Limitations and implications for counselor educators are presented.
Keywords: social justice; advocacy; certificate program; counselor education